California : In Three Dimensions. - California Center for the Arts Museum, Escondido; Bates, Mary; Craigle, Rob; Driscoll, Tom; Grimmer, Mineko; Hawkinson, Tim; Hulett, Tina; Johnson, Jay; Lere, Mark; Mudge, Anne; Nakada, Tomas; Ohira, Minoru; et al. (Escondido : California Center for the Arts Museum, 1995)
Bates, Mary ; Craigie, Rob ; Driscoll, Tom ; Grimmer, Mineko ; Hawkinson, Tim ; Hulett, Tina ; Johnson, Jay ; Lere, Mark ; Mudge, Anne ; Nakada, Tomas ; Ohira, Minoru ; Rudel, Ross ; Shelton, Peter ; Smedley, Melissa ; Therrien, Robert ; Walker, Peter ; Wheeler, Daniel
biografie
California : In Three Dimensions, California Center for the Arts Museum, Escondido, May 21 through August 25, 1995
Engels
boek
Keywords: California